Analisis Partisipasi Masyarakat Lokal dalam Pengelolaan Ekowisata Berkelanjutan di Kawasan Danum Bahandang Kota Palangka Raya - Nurlaila Nurlaila; Ahmad Syahrul Hendrawan; Fitriana Selvia; Imanuel Jaya (Student Research Journal, 2026)
Community participation around tourist destinations is one of the key factors in achieving sustainable conservation-based tourism management. This study aims to analyze the involvement of local communities in the management of sustainable nature tourism in Danum Bahandang, Palangka Raya City. The study employed a qualitative approach with a descriptive design. Data were collected through in-depth interviews with relevant informants, field observations, and documentation studies of various relevant sources. The findings indicate that the level of community involvement in managing the tourist destination remains suboptimal. Local residents only participate in certain tourism activities and have not been actively involved in the planning, management, and decision-making processes related to destination development. This condition shows that the role of the community is still limited and does not yet fully reflect participatory tourism management. Based on Arnstein's ladder of participation theory, the level of community participation falls within the category of *tokenism*. Therefore, greater efforts are needed to enhance community involvement so that sustainable tourism management can be implemented more effectively while supporting environmental sustainability and improving the welfare of local communities.